Health behaviors and multimorbidity resilience among older adults using the Canadian Longitudinal Study on Aging. (January 2020) - Wister, Andrew; Cosco, Theodore; Mitchell, Barbara; Fyffe, Ian
ABSTRACT: Objective: Recently, there has been a growing interest in examining forms of illness-related resilience. This study examines associations between lifestyle behavioral factors and multimorbidity resilience (MR) among older adults. Methods: Using baseline data from the Comprehensive Cohort of the Canadian Longitudinal Study on Aging, we studied 6, 771 Canadian adults aged 65 or older who reported two or more of 27 chronic conditions, and three multimorbidity clusters: cardiovascular/metabolic, osteo-related, and mental health. Associations were explored using hierarchical linear regression modeling, controlling for sociodemographic, social/environmental, and illness context covariates. Results: Among older adults with two or more illnesses, as well as the cardiovascular/metabolic and osteo-related illness clusters, having a non-obese body mass, being a non-smoker, satisfaction with quality of sleep, having a good appetite, and not skipping meals are associated with MR. However, the mental-health cluster resulted in different behavioral lifestyle associations, where MR was not associated with obesity, smoking, or appetite, but inactivity demonstrated moderate positive associations with MR. Discussion: While there are similar patterns of lifestyle behaviors across multimorbidity and multimorbidity clusters involving physiological chronic illnesses, those associated with mental health are distinct. The results have implications for healthy aging among persons coping with multimorbidity.